Comparison between dissection method and coblation technique in tonsillectomy - Joshi, Shreyas S.; Raikar, Vinayak (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: The objective of the present study was to compare the dissection method and coblation technique in tonsillectomy in patients of chronic tonsillitis. Methods: This is prospective study in which 40 patients of chronic tonsillitis in age group of 5-12 years were selected in this study. Patients were blinded with regards to technique used to remove tonsils. 20 patients underwent tonsillectomy by cold dissection method and 20 with coblation method. In both techniques, duration of surgery and amount of blood loss were recorded and compared. Results: In our study, the mean operative time from giving incision to achieving complete haemostasis for dissection method was 42.9 minutes and that for coblation technique was 34 minutes. The amount of blood lost on an average by dissection method was 51.8 ml, and by coblation technique was 22.3 ml. This difference was found to be statistically significant. Pain was evaluated by visual analogue scale. The data recorded from two groups was put to statistical analysis and ‘p’ value was calculated using independent t-test. The mean pain score for coblation technique averaged over 10 days was 2.72 and was 4.84 for dissection technique. Conclusions: We can conclude that coblation tonsillectomy is an easy to learn safe procedure with significant advantages in terms improving the quality of post-operative recovery compared to that following the cold dissection technique. But cost effectiveness of dissection method outweighs benefits of coblation at present in Indian scenario.